2018
DOI: 10.1002/adfm.201800244
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Soft Electromagnetic Actuators for Robotic Applications

Abstract: Electromagnetic actuators (EMAs) serve the majority of motion control needs in fields ranging from industrial robotics to automotive systems and biomedical devices, due to their unmatched combination of speed, precision, force, and scalability. This paper describes the design and fabrication of miniature soft EMAs that operate based on the Lorentz force principle. The actuators are fabricated from silicone polymer, liquid metal (LM) alloy (eutectic gallium indium, EGaIn), and magnetic (NdFeB) powder. They are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 67 publications
0
136
0
1
Order By: Relevance
“…For the gripper type of their E/MA application they reported 0.0049% [16] (p. 8). If the ferromagnetic particles are printed on the soft materials as in Reference [15] (p. 278), it was reported that the power density could range between 22.3 kW/m 3 and 309.3 kW/m 3 , which is the highest reported for untethered soft actuators.…”
Section: Energy Efficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…For the gripper type of their E/MA application they reported 0.0049% [16] (p. 8). If the ferromagnetic particles are printed on the soft materials as in Reference [15] (p. 278), it was reported that the power density could range between 22.3 kW/m 3 and 309.3 kW/m 3 , which is the highest reported for untethered soft actuators.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…However, it could be inferred from the current research that the most convenient scale for the functional robotic prototypes could be at the millimeter level [15,16,35]. In Reference [35], theoretical models for scaling is built and for the sheet-shaped robot, they report difficulty in creating robots that have h < 40 µ m and w < 0.3 mm.…”
Section: Scalability Of E/masmentioning
confidence: 99%
See 3 more Smart Citations